PERLINDUNGAN HUKUM BAGI ANAK HASIL PERKAWINAN CAMPURAN - Niken Utari; Linda Wulandari (JURNAL SUMBER HUKUM, 2025)
Mixed marriages between Indonesian citizens and foreign nationals often raise issues concerning the citizenship status of children born from such unions. This study aims to analyze the citizenship status and legal protection of children resulting from mixed marriages based on Indonesian legislation. The research method used is normative juridical, employing statutory and literature approaches. The results indicate that children from mixed marriages are allowed to hold dual citizenship until the age of 18 and must choose one citizenship by the age of 21. Legal protection provided includes rights to identity, birth certificates, education, healthcare, and inheritance. This protection is ensured by Law No. 12 of 2006 on Citizenship and the Child Protection Law. The state bears a constitutional obligation to guarantee the rights of children from mixed marriages, preventing discrimination and ensuring their welfare and legal certainty. Keywords: legal protection; child; dual citizenship; mixed marriage.